2010
DOI: 10.1002/hipo.20900
|View full text |Cite
|
Sign up to set email alerts
|

Increased adult hippocampal neurogenesis and abnormal migration of adult‐born granule neurons is associated with hippocampal‐specific cognitive deficits in phospholipase C‐β1 knockout mice

Abstract: Schizophrenia is a devastating psychiatric illness with a complex pathophysiology. We have recently documented schizophrenia-like endophenotypes in phospholipase C-β1 knockout (PLC-β1(-/-)) mice, including deficits in prepulse inhibition, hyperlocomotion, and cognitive impairments. PLC-β1 signals via multiple G-protein coupled receptor pathways implicated in neural cellular plasticity; however, adult neurogenesis has yet to be explored in this knockout model. In this study, we employed PLC-β1(-/-) mice to eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 71 publications
(100 reference statements)
9
36
1
Order By: Relevance
“…The integrity of these processes may be crucial for a wide range of sensory and cognitive functions that are impaired in neuropsychiatric diseases (Lewis, 1997). Thus, given the importance of the hippocampus in several psychiatric diseases (Heckers and Konradi, 2010;Tamminga et al, 2010), we wanted to know whether perturbation in a defined adolescent period could affect hippocampal functions in adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integrity of these processes may be crucial for a wide range of sensory and cognitive functions that are impaired in neuropsychiatric diseases (Lewis, 1997). Thus, given the importance of the hippocampus in several psychiatric diseases (Heckers and Konradi, 2010;Tamminga et al, 2010), we wanted to know whether perturbation in a defined adolescent period could affect hippocampal functions in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in the hippocampal GABA system, including a significant reduction in the number of interneurons, reduced GABA-receptor (GABAR) expression, and the disinhibition of pyramidal cells, have been implicated in a variety of neuropsychiatric disorders, including deficient sensorimotor processes (Lewis et al, 2004;Heckers and Konradi, 2010). A recent postmortem study has demonstrated developmental changes in the expression of GABA signaling genes in the hippocampus of normal subjects and this progressive pattern of expression is disturbed in schizophrenic patients (Hyde et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Fitzsimons et al (32) showed glucocorticoid receptor knockdown-induced abnormal dendritic complexity, ectopic positioning of newborn granular cells, and impaired memory consolidation for contextual fear conditioning. Phospholipase C-␤1 knock-out mice exhibited abnormal migration of adult-born neurons, and these mice showed a deficit in hippocampal dependent location recognition task (33). Because the mispositioned neurons in these studies also exhibit other morphological defects, it is still unclear whether these memory deficits are attributed by the mispositioning phenotype alone and/or other morphological phenotypes such as dendritic defects.…”
Section: Nrp2-dependent Cell Positioning Of Newborn Neuronsmentioning
confidence: 95%
“…PLCβ1 has been connected with several human diseases such as leukemia [41] and Alzheimer's disease [42] . It is notable that losses of PLCβ1 are found in patients with neurological disorders such as epileptic encephalopathiess and schizophrenia which are recapitulated in Knock-out mice [43,44] . PLCβ1and G protein signaling are linked to gene regulation.…”
Section: Outline Of Plcβ1 Targets and Pathologymentioning
confidence: 99%